Peran kecambah kacang hijau (Phaseolus radiatus (L.)) pada sel lemak retroperitoneal tikus Sprague Dawley yang diberi diet tinggi lemak - Dwi Lestari; Wiryatun Lestariana; Lily Arsanti Lestari; Arta Farmawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
The role of mung bean sprouts (Phaseolus radiatus (L.)) on retroperitoneal fat cells of Sprague Dawley rats fed a high-fat dietBackground: The tendency of current lifestyles with high consumption patterns of fat is one of the factors causing obesity which is a risk of cardiovascular disease. Prevention of cardiovascular disease can be done by adopting a dietary pattern that is rich in antioxidants including consumption of sources of vitamin E. Sprouts from mung beans contain vitamin E and phytochemicals rich in antioxidants, so they can be used as an alternative to prevent hyperlipidemia sourced from daily functional food.Objective: To assess the effects of mung bean sprouts on retroperitoneal fat weight, cell number and cell diameter in rats fed high-fat feed.Method: This research is an experimental study with a post-test design with the control group. Thirty-four male Sprague Dawley rats ± 2 months old were divided into five groups, group I (standard feed), group II (high-fat feed), group III (high-fat feed and intervention of feeding tube of mung bean sprout 0.67 g/ 200 g BW), group IV (high fat feed and intervention of feeding tube of mung bean sprout 1.34 g / 200 g BW), and group V (high-fat feed and 23 IU dose of vitamin E supplement with feeding tube). After adaptation for three days, the intervention was carried out for four weeks. Analysis of fat weight, fat cell number, and fat cell diameter were done after the treatments. Data analysis using the One-Way ANOVA test. Results: Mung bean sprout dose of 1.34 g given for 4 weeks did not significantly decrease fat weight and cell number, but it decreased the diameter of retroperitoneal fat cells.Conclusion: Mung bean sprouts dose 1.34 g was better than a dose of 0.67 g and vitamin E supplementation in reducing the diameter of retroperitoneal fat cells in rats fed a high-fat diet.